Reduction or discontinuation of antipsychotics for challenging behaviour in adults with intellectual disability: a systematic review - Sheehan, Rory; Hassiotis, Angela (The Lancet. Psychiatry, 2017)
The use of antipsychotics to manage challenging behaviour in adults with intellectual disability is widespread but controversial, and evidence is scarce. There is a perception that antipsychotics used in this context can be reduced or discontinued, and this has been a major focus of recent national policy. However, such an intervention risks harm as well as having potential benefits. We reviewed the available evidence and found that antipsychotics can be reduced or discontinued in a substantial proportion of adults who use them for challenging behaviour, although not always without adverse effects. There is a group which displays behavioural deterioration on antipsychotic reduction that prevents discontinuation; predictors of poor response could not be reliably identified. In view of the relatively scarce data and methodological limitations of the available studies, we cannot draw firm conclusions to inform a population level approach to this issue. Antipsychotic medication used for behaviour should be reviewed regularly and an individualised approach taken to treatment.